2019
DOI: 10.1038/s41598-019-53938-0
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging of Lipids in Human Skin Disease Model Hidradenitis Suppurativa by Laser Desorption Ionization from Silicon Nanopost Arrays

Abstract: Neutral lipids have been implicated in a host of potentially debilitating human diseases, such as heart disease, type-2 diabetes, and metabolic syndrome. Matrix-assisted laser desorption ionization (MALDI), the method-of-choice for mass spectrometry imaging (MSI), has led to remarkable success in imaging several lipid classes from biological tissue sections. However, due to ion suppression by phospholipids, MALDI has limited ability to efficiently ionize and image neutral lipids, such as triglycerides (TGs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 74 publications
2
31
0
Order By: Relevance
“…SEM analysis has been used to monitor the quality of the matrix deposition procedure [ 20 , 21 ] and its influence on the laser ablation process [ 22 ]. Fincher et al [ 23 ] used SEM as a method complementary to MALDI-MSI in their analytical study of lipids in human skin disease. They confirmed the presence of bacteria along the hair shafts on the sick surface.…”
Section: Introductionmentioning
confidence: 99%
“…SEM analysis has been used to monitor the quality of the matrix deposition procedure [ 20 , 21 ] and its influence on the laser ablation process [ 22 ]. Fincher et al [ 23 ] used SEM as a method complementary to MALDI-MSI in their analytical study of lipids in human skin disease. They confirmed the presence of bacteria along the hair shafts on the sick surface.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression of certain sphingolipids such as ceramide and sphingosine-1, that act as biologically active signaling molecules, have been implicated in the pathogenesis of the disease [23]. In a recent report, Fincher et al [24], showed an increased localized accumulation of neutral lipids in HS-infected tissue as a result of a great bacterial load in these lesions. Moreover, recurrence of the disease has been linked to the development of dermic and subcutaneous sinus tracts, and lipids rafts in plasma membranes of keratinocytes also play a role in the regulation of metabolic and proliferative activity of these cells in HS patients [25].…”
Section: Discussionmentioning
confidence: 99%
“… 178 Experiments by Fincher et al have shown that the sensitivity of NAPA-based LDI is in the subfemtomole range, which is significantly more sensitive than techniques involving modification of tissues after mounting on a substrate. 179 Additionally, it is theorized that understanding the effect of array variation on ion yield quantitation is far easier using the NAPA platform as rapid prototyping techniques typically can be optimized to minimize array variation. 180 Nanostructure-initiator mass spectrometry (NIMS) is another technique that utilizes nanostructured surfaces, which use porous silicon to facilitate analyte desorption by laser irradiation.…”
Section: Advances In Single-cell Ms Analysesmentioning
confidence: 99%